(untitled) (Anclajes, 2024)
The first part of this dossier reflected on the dynamics of shame and pride as the articulating axis of the LGTB universe in the Spanish context. This second part takes up that axis of analysis but focuses on four Latin American countries: Mexico, Puerto Rico, Cuba and Argentina. The life stories, autobiographies, poems, letters and press material studied in the different articles confirm the hypothesis that pride is not the dominant experience from the 1970s onwards, nor does shame rule homogeneously in the preceding period. There is, however, a specificity to Latin America –beyond its logical diversity– in the way in which shame and pride are configured among dissident subjects due to the political and socioeconomic circumstances specific to the region. Thus, shame is not only linked to gender and sexuality, but also to social class, race or socio-economic status, while pride also assumes very heterogeneous forms, not always of a public nature, due to the pressure of authoritarian regimes or more conservative societies as a result of machismo and the determining influence of the Catholic religion.